Ghostwalker : Phantom Game - Book 18 - Feehan, Christine (New York : Berkley, 2022)
"Two predators collide with unbridled passion in this intoxicating GhostWalker novel from #1 New York Times bestselling author Christine Feehan. Jonas "Smoke" Harper has watched his brothers find their perfect mates, never imagining he'd actually meet someone who complements every part of him-even the monster that lurks within. But his instant connection with Camellia goes far beyond wanting the intelligent, beautiful, and lethal woman in his bed. They are two parts of a whole, linked to each other and to a larger network that exists everywhere around them. Camellia has lived on her own for a long time, relying on her unique psychic abilities to keep her safe. She knows that Jonas was literally made for her, and that makes their addictive connection more dangerous than a thousand enhanced super soldiers. Once the larger threat looming over them is dealt with she's going to get far away as fast as she can. Life has taught her that the only one she can truly trust is herself. Jonas can sense Camellia is going to run-and the hunter inside doesn't want to let go. Not when he knows how good they'll be together. So he'll just have to use all of his considerable skills to convince her to stay..."--
Keywords: Fantasy fiction